Towards a ritualized public space above divisions: creative (re)construction of children’s rites of passage - Mendel, Maria; Kłonkowska, Anna Maria (Creativity Studies, 2022)
The article refers to anthropological, sociological and pedagogical aspects of reframing – in a creative way – the rituals addressed to children at the threshold of puberty. Based on a presentation of a new ritual of farewell to childhood, the paper is a theoretical reflection on the need of introducing new rituals that create ground for animation-educational practice. This practice – by revivifying creativity in areas considered so far closed and exclusive – makes it possible to overcome socially unfavourable structures of performance, and the inceptions of new, legitimized and empowering forms of subjective representations. Ritual’s creative qualities – in Victor Turner’s conceptualization – have inspired the authors to emphasize the need to replace a hegemony of thinking with a heterogeneity of thinking about the rites of passage. This undertaking is directed towards creating a space in social consciousness for rituals that are other than religious ones. Following Gert Biesta’s thinking, we argue that the farewell to childhood in the form we propose can be seen as an expression of pedagogical interruption and a practice of commonality which is a common good, one endlessly fragile and requiring cultivation. The secular children’s rite of passage and other secular rituals that arise not in opposition to religious rituals, but alongside them, are such common goods.